Pengaruh Metode Cognitive Behaviour Treatment Applied Behaviour Analysis (CBT ABA) Terhadap Kepatuhan Anak Berkebutuhan Khusus Di Klinik Yamet Yogyakarta - Erna Ariyanti Kurnianingsih (Poltekkes Kemenkes Surakarta, 2016)
Abstract : Special Need Children, Applied Behavior Approach, Comformity. Recently, special need children are the most common issue , event somepeople hiding this reality for some reason. It will be a negative impact for all special need children in this country. Special need children being withdrawl and they will depent to other people surround. Instead of that, it’s necesarry to develop an integrated service for special need children to enhanced their skills as independent human being. So they can participate as other people does. Occupational therapist have an important role to help them and improved their independency. The purpose of this research is to know the impact of applied behavior analysis through special need children’s comformity in Yamet Children Private Pratice Yogyakarta. Desain of this research is one-group-pretest-posttest design. This research has a total sampling methode. Result of this research : there is an impact of applied behavior analysis technique through special need children comformity Yamet Yogyakarta.